Efficacy and application study of lipid stain by chromic acid techniques for determining the cause of death from a fat embolism - Chaimad, Yasudama; Witchuvanich, Woratuch (Science, Engineering and Health Studies, 2023)
Fat embolism is a common cause of death after trauma or non-traumatic cases as fat droplets may block blood vessels. It can be identified during autopsy through the microscopic examination of the lungs using Oil Red O (ORO) conducted on frozen tissue, including formalin-fixed tissue. Fat can also be identified using the chromic acid technique. Consequently, in order to increase forensic pathologists' confidence and reduce the cost of delivering ORO stains to other units, the researcher aimed to compare the effectiveness of commercial ORO (ORO-C) and homemade ORO (ORO-HM) in the chromic acid technique for steatosis tissue. We separated the samples into two groups: one stained with ORO-C stain sets and the other with ORO-HM stains. Three experts evaluated the effectiveness of chromic acid stained tissue for both types of ORO using a blind test method. The results were then compared using the SPSS program. The results showed that chromic-ORO-HM of liver had quality and efficiency in interpreting the steatosis detection, similar to the chromic-ORO-C stain sets. Histopathology findings found that fat was paler than chromic-ORO-C stain sets but showed better staining on the background. In addition, chromic acid was able to preserve fat tissue and identify fat-positive results in three victims, who died from fat emboli, suggesting it potential application in forensic medicine.